Research into the phase shift between the waves branched by slots cut through a wide wall of the plane semi-open metal-dielectric waveguide - Афонин, И.Л.; Лащенко, И.В.; Боков, Г.В. (Radiotekhnika, 2012)
Transmission of electromagnetic energy of the centimetre wave range is carried out mainly through the waveguides of rectangular section and strip lines. The plane semi-open metal-dielectric waveguide can serve as alternative to these devices. To estimate the parameters of the devices developed on the basis of this waveguide the measuring instrument is offered, the two-detection waveguide and slotted-guide converter is the basis of its microwave part. The principle of operation of this transformer requires a quasi-constancy of phase deviation in the frequency band. An invariance of phase drift is possible to achieve by distance alteration between slots, and change of an angle of their pitch.